Discovery of a small molecule RXFP3/4 agonist that increases food intake in rats upon acute central administration. Issue 8 (15th April 2019) - DeChristopher, Brian; Park, Soo-Hee; Vong, Linh; Bamford, Derek; Cho, Hyun-Hee; Duvadie, Rohit; Fedolak, Allison; Hogan, Christopher; Honda, Toshiyuki; Pandey, Pramod; Rozhitskaya, Olga; Su, Liansheng; et al.
Graphical abstract: Abstract: The relaxin family peptide receptors have been implicated in numerous physiological processes including energy homeostasis, cardiac function, wound healing, and reproductive function. Two family members, RXFP3 and RXFP4, are class A GPCRs with endogenous peptide ligands (relaxin-3 and insulin-like peptide 5 (INSL5), respectively). Polymorphisms in relaxin-3 and RXFP3 have been associated with obesity, diabetes, and hypercholesterolemia. Moreover, central administration of relaxin-3 in rats has been shown to increase food intake, leading to body weight gain. Reported RXFP3 and RXFP4 ligands have been restricted to peptides (both endogenous and synthetic) as well as a low molecular weight positive allosteric modulator requiring a non-endogenous orthosteric ligand. Described here is the discovery of the first potent low molecular weight dual agonists of RXFP3/4. The scaffold identified is competitive with a chimeric relaxin-3/INSL5 peptide for RXFP3 binding, elicits similar downstream signaling as relaxin-3, and increases food intake in rats following acute central administration. This is the first report of small molecule RXFP3/4 agonism.